2020
DOI: 10.1055/s-0040-1718244
|View full text |Cite
|
Sign up to set email alerts
|

Does Periodontal Treatment Help in Arterial Hypertension Control? A Systematic Review of Literature

Abstract: Arterial hypertension and periodontal diseases are two of the pathologies with more prevalence worldwide. In the last few years, several scientific evidences have demonstrated the relationship between both diseases. Besides the etiopathogenic and causal relationship, some recent publications have pointed out that the therapeutic approach of periodontitis could have positive effects on the control of arterial hypertension.The aim of this systematic review is to determine whether there is a decrease in or better… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…64,65 C. albicans and nonalbicans Candida species have a positive correlation with immunosuppression, [66][67][68] H. pylori and phyla proteobacteria 67 have a positive correlation with gastritis, and P. gingivalis has been positively related to cardiovascular diseases. 66,67 Knowledge of changes in oral microbiota and their relation to GI microbiota is very important. The oral cavity can act as an extra gastric pool for many microorganisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…64,65 C. albicans and nonalbicans Candida species have a positive correlation with immunosuppression, [66][67][68] H. pylori and phyla proteobacteria 67 have a positive correlation with gastritis, and P. gingivalis has been positively related to cardiovascular diseases. 66,67 Knowledge of changes in oral microbiota and their relation to GI microbiota is very important. The oral cavity can act as an extra gastric pool for many microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…64 Whereas, Megasphaera micronuciformis and C. albicans, to some extent, have a negative correlation with caries. 64,65 C. albicans and nonalbicans Candida species have a positive correlation with immunosuppression, [66][67][68] H. pylori and phyla proteobacteria 67 have a positive correlation with gastritis, and P. gingivalis has been positively related to cardiovascular diseases. 66,67 Knowledge of changes in oral microbiota and their relation to GI microbiota is very important.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in dentistry have reported that patients with periodontitis have higher blood pressure 17 19 . It is estimated that severe periodontal diseases are prevalent in around 14% of the global adult population, representing more than one billion cases over the world 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in dentistry have reported that patients with periodontitis have higher blood pressure [17][18][19] . An estimated mechanism for the association between periodontitis and hypertension is endothelial dysfunction elicited by periodontitis 20 .…”
Section: Introductionmentioning
confidence: 99%